Synthesis and characterisation of ultrasound imageable heat-sensitive liposomes for HIFU therapy. (18th August 2015) - Maples, Danny; McLean, Kevin; Sahoo, Kaustuv; Newhardt, Ryan; Venkatesan, Perumal; Wood, Bradford; Ranjan, Ashish
Abstract: Background/Objective : Novel approaches allowing efficient, readily translatable image-guided drug delivery (IGDD) against solid tumours is needed. The objectives of this study were to: 1) develop echogenic low temperature sensitive liposomes (E-LTSLs) loaded with an ultrasound (US) contrast agent (perfluoropentane, PFP), 2) determine the in vitro and in vivo stability of contrast agent encapsulation, 3) co-encapsulate and characterise doxorubicin (Dox) E-LTSL, and cellular uptake and cytotoxicity in combination with high intensity focused ultrasound (HIFU). Method : E-LTSLs were loaded passively with PFP and actively with Dox. PFP encapsulation in E-LTSL was determined by transmission electron microscopy (TEM), and US imageability was determined in tissue-mimicking phantoms and mouse tumour model. Dox release from E-LTSL in physiological buffer was quantified by fluorescence spectroscopy. Cellular uptake and cytotoxicity of E-LTSL in the presence of HIFU-induced mild hyperthermia (∼40–42 °C) was determined in a 3D tumour spheroid model. Results : TEM and US confirmed that the PFP emulsion was contained within LTSLs. Phantom and animal studies showed that the E-LTSLs were echogenic. Temperature versus size increase and Dox release kinetics of E-LTSLs demonstrated no difference compared to LTSL alone. Dox release was <5% within 1 h at baseline (25 °C) and body (37 °C) temperatures, and was >99% under hyperthermia. E-LTSL plus HIFU achieved significantly greater Dox uptake in spheroids and cytotoxicity compared to body temperature. Conclusion : A stable US-imageable liposome co-loaded with Dox and PFP for in vivo IGDD was developed. Data suggest that HIFU can induce cellular uptake and toxicity with E-LTSLs.